Implementasi UU Kesehatan dan Tantangan Lex Specialis terhadap Doktrin Mater Semper Certa Est dalam Penetapan Status Ibu dalam “Surrogate Agreement” - Jeisika Laurens; Gunawan Widjaja (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
. Surrogacy practices in Indonesia have created a conflict of legal norms between the doctrine of mater semper certa est, as stipulated in Article 250 paragraph (3) of the Indonesian Civil Code, and the new provisions introduced under Health Law No. 17 of 2023. This normative legal research aims to compare the regulation of surrogacy in Indonesia, the Netherlands, and the United Kingdom in order to identify an appropriate legal solution to the existing normative conflict. The analysis demonstrates a fundamental similarity among the three jurisdictions in permitting altruistic surrogacy, particularly arrangements that do not involve commercial compensation. However, a significant difference is found in the legal mechanisms used to determine and transfer maternal status. In the Netherlands and the United Kingdom, the transfer of legal motherhood requires a court ruling issued after the child is born. In contrast, Indonesia adopts a conceptual and administrative transfer mechanism established from the beginning of the surrogacy agreement based on the principle of lex specialis. Although these new regulations provide a clearer legal basis for recognizing the intended mother, future challenges will involve synchronizing civil registration systems and harmonizing implementing regulations to ensure legal certainty and effective application in practice.